Wacana Homo Nationalis dalam Iklan Minuman NutriSari Heritage - Adek Risma Dedees (Program Studi Ilmu Komunikasi, 2013)
Discourse of homo nationalist or ‘nationality’ at NutriSari Heritage drinking ads is fulled by construction of ‘national identity’ as a part of Indonesian ‘nation’. This ads explains refraction or ‘pseudoisation’ of ethnicity of representation on discourse of homo nationalist as implication because of be valued majority or fulled by highest valued (luhung). The refraction might happened because of existence stereotyping toward ethnicity of nation certain. Stereotyping is produced, reproducted, guarded, kept, and even preserved in multiple discourses, in this case at drinking advertisement. Method of this research is qualitative-interpretative within used critical discourse analysis approach. This research use Ruth Wodak critical discourse analysis modal. It is used for interpretating and elaborating homo nationalist discourse in narration constructing of ‘nationhood’.